1988
DOI: 10.1149/1.2096214
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Film Oxidation‐Undercut Kinetics

Abstract: A process is presented for fabricating micromechanical structures or freestanding shapes such as sheets of polysilicon. A sacrificial layer of carbon is deposited on a substrate, followed by a top layer of a second material. After oxidation of the carbon, the top layer is left free. The kinetics of the diffusion-limited oxidation process are modeled and compared to experimental data for the undercut of large (17 • 8.6 cm) sheets of polysilicon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Furnace induced temperature error, measured by suddenly shutting off the furnace, was less than 20~ and was compensated by calibrating the pyrometer during test runs with thermocouples embedded in the boxes. Thus box temperature could be controlled to within 10~ After silicon deposition, the boxes were unloaded and the partitions were loaded in stacks into semiconductor oxidation furnaces at 1000~ There, the carbon layers were oxidized, freeing the silicon sheets (2). The polysilicon sheets were zone melted with CO2 lasers to increase grain size, and then used as feedstock in a solar cell process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furnace induced temperature error, measured by suddenly shutting off the furnace, was less than 20~ and was compensated by calibrating the pyrometer during test runs with thermocouples embedded in the boxes. Thus box temperature could be controlled to within 10~ After silicon deposition, the boxes were unloaded and the partitions were loaded in stacks into semiconductor oxidation furnaces at 1000~ There, the carbon layers were oxidized, freeing the silicon sheets (2). The polysilicon sheets were zone melted with CO2 lasers to increase grain size, and then used as feedstock in a solar cell process.…”
Section: Methodsmentioning
confidence: 99%
“…Using the ion milling method, there is a redeposition layer problem (2). When the angle of the cross-sectional shape of the photoresist pattern is large, the redeposition layer grows on the sidewall of the photoresist pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, these equations have been solved analytically by several authors (6)(7)(8)(9)(10)(11)(12). The first step is to derive an expression for x f /L .…”
Section: Oxidation Modelingmentioning
confidence: 99%
“…Additionally, for carbon film undercut oxidation kinetics used for describing the fabrication of micromechanical structures 5 , it was shown that the present model should provide a better description of the low temperature kinetics. The possible use of the counter-current gaseous diffusion model was also described for CVI.…”
mentioning
confidence: 93%